Isolation of methicillin resistant staphylococcus aureus from the environmental samples in Dhaka City - Farheen, Saria (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.